Magnetic Resonance Visibility, Artifacts, and Overall Safety of the Self-Locating Peritoneal Dialysis Catheter with a Tungsten Tip. (24th January 2023) - Gallieni, Maurizio; Rossi, Umberto G.; Tonolini, Massimo; Ianniello, Andrea; Miglio, Roberta; Sabiu, Gianmarco; Cariati, Maurizio
Abstract : Background . The self-locating peritoneal dialysis (PD) catheter, contains a tungsten tip. The effects of magnetic resonance (MR) on the catheter were evaluated, emphasizing its MR signal, artifacts, ferromagnetism, and possible heating production during the MR sequences. Methods . The catheter was studied in an ex vivo model using a 1.5T MR system and placed into a plastic box containing saline solution. Acquisitions on coronal and axial planes were obtained on fast gradient-echo T1-weighted and fast spin-echo T2-weighted. In vivo abdominal MR exams were also carried out. Results . Overall, the catheter had good visibility. In all sequences, an extensive paramagnetic blooming artifact was detected at the level of the tip tungsten ballast, with a circular artifact of 5 cm in diameter. The catheter showed no magnetic deflection, rotation, or movements during all MR sequences. After imaging, the temperature of the saline solution did not change compared to the basal measurement. Patients safely underwent abdominal MR. Conclusions . The results point to the possibility of safely performing MR in PD patients carrying the self-locating catheter. The self-locating PD catheter is stable when subjected to a 1.5T MR system. However, it creates some visual interference, preventing an accurate study of the tissues surrounding the tungsten tip.